Content-Based Image Retrieval Techniques: A Survey. Issue 4 (July 2021) - Sivakumar, M; Saravana Kumar, N M; Karthikeyan, N
Abstract: In these eras, digital day's cell smartphones and cameras are gaining a titanic reputation, resulting in the speedy growth of virtual images that are available throughout the internet. With an exponential boom within the image sizes, databases in different media lie an extremely good project for massive scale image search. Image retrieval from databases or the internet wishes an unsuccessful and effective technique because of the explosive increase of digital snapshots. Image recovery is known to be a comprehensive research area, particularly in content-based image retrieval (CBIR). CBIR retrieves comparable photographs from a huge photograph database primarily based on photo features, which has been totally lively study vicinity recently. The content materials that may be derived from images which include color, shade, texture, shape, are used for retrieving an image from the database. This paper will provide a survey and discuss the contemporary literature of various sorts of image retrieval (IR) structures and comparisons among them.